FAKTOR-FAKTOR DOMINAN YANG MEMPENGARUHI KEBERDAYAAN WANITA DALAM MENGEMBANGKAN INDUSTRI RUMAH TANGGA BERBAHAN BAKU SAGU DI KECAMATAN TEBING TINGGI TIMUR KABUPATEN KEPULAUAN MERANTI - Yenny Cinantri Purba; Eri Sayamar; Rosnita Rosnita (Fakultas Pertanian, Universitas Riau, 2020)
This study aims to (1) describe the home industry made from sago, and (2) to analyze the dominant factors that influence women's empowerment in developing household industries made from sago. This research was conducted in Tebing Tinggi Timur District, Kepulauan Meranti Regency from December 2017 to May 2018 using snowball sampling. The number of samples in this study were 14 people, where all respondents produced liquid sugar, but there were also respondents who produced refined sugar and sago crackers. The data analysis used in this research is descriptive analysis and multiple linear regression. The results showed: (1) Home industry players made from sago are at a productive age with a low level of education (SD 78.57%) and business experience is still under 1 year (85.71%) which on average use 1 person in labor. The main raw material is obtained from UP2K sago refineries or refineries around industrial locations, at a price of Rp. 2,000 / Kg. The average production of liquid sugar, powdered sugar and sago crackers produced by business actors is 3 bottles, 4 packs and 3.5 kg per production process. Business capital entirely uses the capital itself and product marketing is carried out by adjusting the product by word of mouth and cooperation with agents (stalls). (2) The dominant factor that influences women's empowerment in developing a home industry made from sago is the human resource and institutional variables that have a significant or real effect.